Development of Graves' Disease After SARS-CoV-2 mRNA Vaccination: A Case Report and Literature Review - Lui, David Tak Wai; Lee, Ka Kui; Lee, Chi Ho; Lee, Alan Chun Hong; Hung, Ivan Fan Ngai; Tan, Kathryn Choon Beng (Frontiers in Public Health, 2021)
Background: Mounting evidence has revealed the interrelationship between thyroid and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to explain the thyroid dysfunction and autoimmune thyroid disorders observed after coronavirus disease 2019 (COVID-19). There are limited reports of thyroid dysfunction after SARS-CoV-2 vaccination. Methods: We report a case of a 40-year-old Chinese woman who developed Graves’ disease after BNT162b2 mRNA vaccine. A search of PubMed and Embase databases from 1 September 2019 to 31 August 2021 was performed using the following keywords: ‘COVID’, ‘vaccine’, ‘thyroid’, ‘thyroiditis’ and ‘Graves’. Results: A 40-year-old Chinese woman who had 8-year history of hypothyroidism requiring thyroxine replacement. Her anti-thyroid peroxidase and anti-thyroglobulin antibodies were negative at diagnosis. She received her first and second doses of BNT162b2 mRNA vaccine on 6 April and 1 May 2021 respectively. She developed thyrotoxicosis and was diagnosed to have Graves’ disease 5 weeks after the second dose of vaccine, with positive thyroid stimulating immunoglobulin level, diffuse goitre with hypervascularity on thyroid ultrasonography and diffusely increased thyroid uptake on technetium thyroid scan. Both anti-thyroid peroxidase and anti-thyroglobulin antibodies became positive. She was treated with carbimazole. Literature search revealed 4 cases of Graves’ disease after SARS-CoV-2 vaccination, all after mRNA vaccines; and 9 cases of subacute thyroiditis, after different types of SARS-CoV-2 vaccines. Conclusion: Our case represents the fifth in the literature of Graves’ disease after SARS-CoV-2 vaccination, with an unusual presentation on a longstanding history of hypothyroidism. Clinicians should remain vigilant about potential thyroid dysfunction after SARS-CoV-2 vaccination in the current pandemic.